Unravelling the risk factors and treatment patterns of dyslipidemia in India (UNICORN study) - Mayabhate, Mayur; Sharma, Akhilesh (International Journal of Research in Medical Sciences, 2024)
Background: The UNICORN study aims to determine the risk factors and patient demographics for dyslipidemia and assess the efficacy of the prevalent therapies in managing dyslipidemia. Methods: The UNICORN study employed a retrospective cross-sectional design, analyzing data from 9,998 patient health records retrieved from tertiary care centers across India. Demographic variables, lipid profile parameters, risk factors (smoking status, alcohol consumption and dietary habits) and healthcare-related variables (treatment history of medication, lifestyle interventions and lipid profiles) were extracted from medical records. Descriptive statistics and hypothesis testing were used to assess lipid profiles, comorbidities and treatment impact. Odds ratios and paired t-tests evaluated morbidity risk and treatment efficacy. Results: Statins were prescribed to 99.19% of the patients. 61.61% of the population did not follow any particular diet. Lipid parameters were better in obese and overweight patients, compared to normal and underweight patients (p<0.001). Patients with hypertension (239.5 vs 223.4 mg/dl), coronary artery disease (240.5 vs 231.4 mg/dl), stroke (230.3 vs 236.3 mg/dl) and peripheral arterial disease (238.1 vs 234.1 mg/dl) showed significantly higher total cholesterol levels. The odds ratio (OR) reported a higher likelihood of newly diagnosed patients developing hypertension (OR=1.76), coronary artery disease (OR=1.65), heart failure (OR=1.76), stroke (OR=1.82) and peripheral arterial disease (OR=1.71). Conclusions: Statins were used by the majority of the patients and improved the serum lipid levels. However, the improved lipid measures were still indicative of dyslipidemia, with the absence of complete resolution of the condition. Hypertension, coronary artery disease, stroke and peripheral arterial disease are risk factors and frequently associated comorbidities with an unclear causal relationship.